Nerita undata (Linnaeus, 1758) as bioindicator of imposex in the coastal barangay of Palanas, Ginatilan, Cebu - Dugaduga, Jelly O. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The occurrence of imposex in a shipping dock in Barangay Palanas, Ginatilan, Cebu was investigated by collecting Nerita undata snails. Imposex involves endocrine disruption in which female gastropods develop sexual features of males such as penis or vas deferens. This can be caused by tributyltin (TBT) compounds which is a toxic organotin compound found in naval paints for boats and artificial structures. A total of 30 Nerita undata snails were randomly collected from the sampling site; 17 were males while 13 were females. The sizes of the snails and the penis length of male Nerita undata snails were measured. There is no significant difference in the shell length of male and female snails. The mean penis length of male snails is 1.38 mm. After sex determination, there was no observed imposex occurrence among female Nerita undata snails suggesting that the amount of concentration of organotin compounds in the area is much lesser for it to have effects on the reproductive part of female Nerita undata present in the area.